2016
DOI: 10.1021/acs.chemmater.6b00115
|View full text |Cite
|
Sign up to set email alerts
|

Metal Nanoparticle-Loaded Microgels with Selective Permeability for Direct Detection of Small Molecules in Biological Fluids

Abstract: We report a microfluidic strategy for creating semipermeable microgels containing metal nanoparticles to directly detect small molecules included in the solution of large adhesive proteins using surface-enhanced Raman scattering. With a capillary microfluidic device, gold nanoparticle-laden microgels are prepared to have uniform size. The microgels allow diffusion of smaller molecules than mesh size of their gel network while excluding larger molecules. This enables the selective infusion of small analytes ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Therefore, the LOD is estimated as 10 −10 m . In a comparison, the microgels with Δ C = 0 has the LOD of 10 −8 m according to our previous work, which is two orders of magnitude larger; this is roughly consistent with the intensity enhancement factor of 78.4 for the microgels with the concentration factor of 33.2.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, the LOD is estimated as 10 −10 m . In a comparison, the microgels with Δ C = 0 has the LOD of 10 −8 m according to our previous work, which is two orders of magnitude larger; this is roughly consistent with the intensity enhancement factor of 78.4 for the microgels with the concentration factor of 33.2.…”
Section: Resultssupporting
confidence: 88%
“…To study of the influence of BSA, the microgels are suspended in the solution of 10 −7 m R6G only. Raman intensity from unary solution of R6G is comparable with that from binary solution of R6G and BSA, indicating that there is no interruption of BSA for measuring Raman spectrum of R6G; it has been reported that BSA adsorbs on the surface of Au NPs and leads to a drastic reduction of Raman intensity when free Au NPs are directly dispersed in the binary solution of R6G and BSA …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The size-selective separation of analytes is useful for detecting small molecules dispersed in a mixture, such as human blood or commercial beverages. Hydrogels can separate target molecules from a mixture using their small mesh size [ 82 ]. Molecules with a size smaller than the mesh size of the hydrogel can diffuse into a gold nanoparticle-encapsulated hydrogel, whereas larger materials are excluded.…”
Section: Sers-based Sensor Applicationsmentioning
confidence: 99%
“…SERS has been considered as an attractive technique for the sensitive and selective detection of biomolecules because of its single molecule level sensitivity, molecular specificity, and insensitivity to quenching . Recently, Yang and co‐workers and Cui and co‐workers reported SERS based telomerase activity detection methods using Au NPs.…”
Section: Resultsmentioning
confidence: 99%